Analisis Konstruksi Framing Berita Kekerasan Seksual Pada Media Cnnindonesia.Com Dan Kompas.Com (Edisi September-Oktober 2021) - Fadilah, Aisyah Asharini Nur; Setiawan, Hendra; Maspuroh, Uah (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
The mass media have a big role in distributing news to the public, therefore it is important for the mass media to package news appropriately, according to facts, as well as objective and professional. This research, which is a descriptive qualitative research, aims to explore the framing constructed by online mass media CNNIndonesia.com and Kompas.com on the topic of sexual violence regarding father abuse of children in Luwu Timur which was reported on October 7, 2021. The data selected were based on purposive techniques. sampling which is the first report so that it can analyze how the two media construct language on reporting on sexual violence with limited information. This study uses the framing theory of Zhongdang Pan and Gerald M. Kosicki. The results of this study indicate that the two media form a provocative impulse but use language that is in accordance with the rules of mass media. The two media also collided with two sources in the news who exchanged differences of opinion regarding the closed harassment case. Keywords: framing analysis, news text construction, sexual violence, mass media